Development of extraction technology by supercritical carbon dioxide of rice bran oil to industrial level in the Majes Valley - Fernando Mejía Nova (2019)
Rice is one of the products with great economic importance in the southern region of our Country, mainly in the area of Corire, Arequipa region, which has successfully developed high yields mainly varieties IR 43 and Tacuarí. In order to take advantage of the products of husped rice, such as bran, we proposed an oil extraction technique by supercritical fluid which allows us to extract oil by means of high pressure and low temperatures. Initially a machine of supercritical fluids 100 ml capacity in the laboratory allowing the search for oil extraction parameters achieving yields close to 20% , then the design and construction of a machine of 04 liters of capacity with successful results. The research was conducted with support from FINCYT, Chapí Rice Mill Company and institutions like the Universidad Católica de Santa Maria and the Instítuto de Investigacion del Sur.